Management of sesame phyllody: Adestructive disease of South-western Rajasthan: Sesame Phyllody Management - Sharma, Jitendar Kumar; Lekha; Shekhawat, H V S; Joshi, Neeshu; Meena, Vijay Kamal; Sharma, Kapil (Annals of Arid Zone, 2023)
Various factors cause yield loss of sesame (Sesamum indicum L.) and among them sesame phyllody is a major one. Present field study showed the variable reactivity by sesame phyllody pathogen to insecticides, combination of phytoextract with insecticide and combination of antibiotic with insecticide as seed treatment and foliar spray. Seed treatment with Imidacloprid 17.8% SL @ 3 mL kg-1 seed followed by its two foliar sprays of @ 150 mL ha-1 were most effective. The per cent disease incidence came down from 33.33 in control to 5.55% after first spray and from 42.22 in control to 7.78% after second spray. Area under disease progress curve (AUDPC) was minimum (133.30) and per cent disease control (81.58%) was maximum. As a result yield of sesame obtained (543 kg ha-1) was maximum. This effect of the above treatment was at par with that of Thiomethoxam 25% WG @ 100 g ha- 1. Thiomethoxam application reduced disease incidence to 7.78% and 12.22% after first and second spray respectively, with AUDPC being 200.00. It showed 71.05% disease control and resulted in the sesame yield of 520.67 kg ha-1.